BLACK CINEMA AS AN ANTI-RACIST PRACTICE: NARRATIVES OF THE NIGERIAN CIVIL WAR IN ENGLISH LANGUAGE CLASSES - Geisler, Maeles Carla; Galarça, Sandro Lauri da Silva (Seven Editora, 2026)
Law 10.639/03 on education for ethnic-racial relations is 22 years old since its approval. In order to make visible actions aimed at anti-racist education, this research presents an account of an experience with anti-racist practices. The objective is to highlight aspects that can be developed in students with these practices aimed at ethnic-racial education, working with Black cinema. Through an account of experience, assumptions from educational theorists (Freire, 2015; 2024; hooks, 2017), media theorists (Belloni, 2009; Jenkins, 2022), anti-racist education theorists (Cavalleiro, 2024), and ethnic-racial issues theorists (Munanga, 2009; 2015; Ribeiro, 2018), among others who discuss the topic, are interwoven. The film used in class is “Half of a Yellow Sun” (2013) by Nigerian director Biyi Bandele, an adaptation of the novel “Half of a Yellow Sun” (2006) by Nigerian writer Chimamanda Ngozi Adichie. The central theme of the historical novel, and also of the film, is the Nigerian Civil War (1967-1970). The story begins with the country’s independence in 1960 and shows the events leading up to the conflict, depicting the lives of the characters before the war until its end in 1970. Given the extent of the problem of racism in our society, education focused on ethnic-racial relations is urgently needed. This set of practices in basic education becomes fundamental in combating racial prejudice against Black people and in valuing Black personalities, working with their artistic, scientific, and intellectual productions in the classroom and incorporating them into the curriculum. Cinema, by awakening sensibilities through aesthetic experiences, can play an important role in strengthening Black identity, promoting the recognition of students’ cultural roots and valuing their connection to their own origins and sense of belonging. DOI: https://doi.org/10.56238/sevened2026.001-028